Estudo das propriedades eletrônicas, energéticas e estruturais de moléculas adsorvidas em estruturas 1D e 2D de SiC - Oliveira, Joao Batista de (2014)
In this work, we performed an ab initio study of interaction between several molecules with SiC nanotubes and SiC Sheets, with focus on benzene molecule. performed too a study the mechanical and electronic properties of SiC nanowires(SiCNWs). For study the interaction of molecules with SiCNTs and SiCSheets, we considered two possibilities, (1) molecules adsorbed on SiCNT/SiCSheet surface, and (2) molecules encapsulated by SiCNT. We have considered several geometries for adsorption and dierent nanotube chiralities. For study of mechanical and electronics properties of SiCNWs, we considered 3C-, 2H, 4H and 6H-SiCNW, analyzing the eects of the diameter on these properties. All calculations were performed by using the Density Funcional Theory, using de the Local Density Approximation (LDA). The electron-ion interaction was describe by using norm-conserving pseudopotentials. For the benzene adsorption on the SiCNT, we nd an exothermic process, with binding energies between 0.3 and 0.4 eV/molecule, and for benzene encapsuladed we nd binding energies of 0.6 eV/molecule, revealing a preference for the benzene encapsulated systems. For both cases, we verify that there are not chemical bonds at the benzene- SiCNT/SiCSheet interface, and the interaction of benzene molecule with nanotube and Sheet is mediated by pi stacking interactions, similar to the benzene-CNT systems. For both cases, we verify that SiCNTs are more reactive than the carbon nanotube (CNTs) For nanowires study, our results show that all nanowires investigated exhibit direct band gaps, in contrast with the indirect band gap observed in Bulk SiC. The study of eect of unixial stress on the electronic properties of nanowires, reveal that band-gap dependence on the strain is dierent for each nanowire type. For the mechanicals properties, our results revels that Youngs moduli of nanowires show strong dependece on the diameters, and the 2H-SiCNWs are stier than than other nanowires with similar diameter. The values for Youngs moduli of dierent SiCNWs, revels that they are more stifer than nanowires of other elements, for example Si, InAs and Ge.